Antifungal effect of piper betle (sireh) leaf extract on selected fungal species of pathogenic otomycosis in in-vitro culture medium - Abdullah, Ardhi (2018)
Introduction: Otomycosis is an infection of the ear by the fungal species. The prevalence keeps increasing due to the widespread use of broad-spectrum antibiotics, steroids and other chemotherapeutic agents. Piper betle leaf has been used extensively as a traditional healing by old folk. Piper betle leaves extracts has potential to act as an antifungal medication but not been studied. This is a pilot study which analyses antifungal properties of Piper betle leaves towards pathogenic otomycosis, particularly Candida albicans and Aspergillus niger. Objective:To study the antifungal effect of Piper betle leaf extracts on Aspergillus niger and Candida albicans by determining inhibitory efficacy and comparing antifungal activity of different concentration of Piper betle leaf aqueous and alcohol extracts on Aspergillus niger and Candida albicans Methodology: This is a laboratory-controlled prospective study. Results: Both Aspergillus niger and Candida albicans showed sensitivity to aqueous and alcohol Piper betle leaf extracts. Mean zone of inhibition increase in proportion to extract concentration. Statistically, one-way ANOVA showed significant mean differences between groups of concentration for both aqueous and alcohol extracts. Independent t-test was applied to compare mean between two groups. Conclusion:.Piper betle leaf extract has potent antifungal activities on Aspergillus niger and Candida albicans. The antifungal efficacy in aqueous solution is better than alcohol solution.